1990
DOI: 10.1017/s0022112090001124
|View full text |Cite
|
Sign up to set email alerts
|

A purely elastic instability in Taylor–Couette flow

Abstract: A non-inertial (zero Taylor number) viscoelastic instability is discovered for Taylor–Couette flow of dilute polymer solutions. A linear stability analysis of the inertialess flow of an Oldroyd-B fluid (using both approximate Galerkin analysis and numerical solution of the relevant small-gap eigenvalue problem) show the growth of an overstable (oscillating) mode when the Deborah number exceeds f(S) ε−½, where ε is the ratio of the gap to the inner cylinder radius, and f(S) is a function of the ratio of solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
455
3
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 489 publications
(494 citation statements)
references
References 33 publications
33
455
3
3
Order By: Relevance
“…We speculate, but cannot confirm, that this flow oscillation may be directly linked to the longest fluid relaxation time ( ). This analysis is consistent with prior work that also reports oscillatory elastic instabilities in stressed viscoelastic fluids [10,12,20]. We believe that the instabilities observed in our experiments occur in regions where p = s p _ _ = s _ > 1, where p ÿ s p _ _ is the elastic stress and s s _ is the viscous stress.…”
supporting
confidence: 93%
“…We speculate, but cannot confirm, that this flow oscillation may be directly linked to the longest fluid relaxation time ( ). This analysis is consistent with prior work that also reports oscillatory elastic instabilities in stressed viscoelastic fluids [10,12,20]. We believe that the instabilities observed in our experiments occur in regions where p = s p _ _ = s _ > 1, where p ÿ s p _ _ is the elastic stress and s s _ is the viscous stress.…”
supporting
confidence: 93%
“…Less well understood are flow instabilities in complex fluids. The unusual non-Newtonian flow properties of complex fluids can not only modify existing instabilities such as viscous fingering [1] but they can also give rise to completely new instabilities and flow behavior [2][3][4][5][6][7][8]. In this Letter we present evidence that a viscoelastic flow instability that is absent for Newtonian fluids underlies an important set of phenomena that occur in the spinning of polymer fibers, and that have plagued the plastic industry ever since the first plastic fibers were produced.…”
mentioning
confidence: 85%
“…Grillet et al, 1999;Joo and Shaqfeh, 1992;Graham, 2003) have been studied in single roll coating applications. Furthermore detailed studies in the Taylor-Couette geometry have shown that in addition to purely elastic instabilities arising from streamline curvature (Larson et al, 1990;Muller et al, 1989), weak elastic effects may stabilize or destabilize inertially-driven flow transitions. These competing effects can be represented by stability loci plotted on a diagram of the critical Deborah number versus critical Reynolds number.…”
Section: Discussionmentioning
confidence: 99%